Effects of Partial Organic Fertilizer Substitution on Grain Yield, Nitrogen Use Efficiency, and Physiological Traits of Rice in Northeastern China - Shimeng Guo; Yimeng Li; Zhouzhou Wu; Jiaxin Liu; Chao Liang; Yue Wang; Shu Wang; Chanchan Zhou; Junfeng Liu; Jingyi Mu (Agronomy)
In China, agriculture is currently highly dependent on chemical nitrogen. This leads to low nitrogen use efficiency and high nitrogen losses. Considering the issues caused by excessive chemical fertilizer, integrated nutrient management using organic and chemical fertilizer sources is important. To clarify how partial substitution of chemical fertilizer by organic fertilizer affects rice yield, physiological traits, and nitrogen use efficiency, we conducted a two-year field trial in 2021 and 2022, and used two rice cultivars, Shendao47 (SD47) and Shendao505 (SD505), which were grown in the field with five fertilization treatments: (1) CK (zero N application); (2) CF (100% chemical fertilizer); (3) OR10 (10% organic fertilizer + 90% chemical fertilizer); (4) OR20 (20% organic fertilizer + 80% chemical fertilizer); and (5) OR30 (30% organic fertilizer + 70% chemical fertilizer). The results show that the partial organic substitution (OR) treatments improved the yield by 1–10% for two cultivars by increasing effective panicles and grain filling. The increase in grain filling was related to the photosynthetic parameters, including LAI, chlorophyll content, and net photosynthetic rate during the grain-filling stage. The photosynthetic parameters of OR treatments were higher than those of CF treatment. Additionally, with the increase in organic fertilizer application rates, the grain yield, agronomic N use efficiency, partial factor productivity of applied N, and physiological N use efficiency increased at first and then decreased, peaking in OR20 treatment. Conclusively, the 20% organic fertilizer with 80% chemical fertilizer is a promising option for higher yield and improved N utilization for both cultivars. This study provides a sustainable nutrient management strategy to improve crop yield with high nutrient use efficiency.